PENGARUH LATIHAN LARI NAIK-TURUN TANGGA TERHADAP DAYA TAHAN ATLET SILAT PUTRA PERGURUAN TAPAK SUCI PEKANBARU - Riswandi Riswandi; Zainur Zainur; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Based on observations from observers and interviews with trainers at Pekanbaru Tapak Suci College, martial arts athletes are still found with deficits that are affected by physical conditions, including the endurance of poor athletes, especially male athletes. How fast the athlete gets tired during the competition before the whistle sounds, a situation often occurs. Based on the t-test analysis statistics, the difference is 0.79 and the t-count produces 4.2450 and t-table 1,860. Number of sources> t-table. It can be concluded that kicking up and down, done 16 times, has an effect on the endurance of female athletes from Pekanbaru's Tapak Suci University. Based on the results of the analysis and processing of the data above, the following conclusions can be drawn: there is a significant effect between up and down training (X) on endurance (Y) in male athletes at Pekanbaru Tapak Suci University.Key Words: Ladder-Running Runs To Atlock Silat Resistant Power